Targeting super-enhancers in liver cancer: from pathogenic mechanisms to clinical applications - Li, Chang-Lei; Yao, Zhi-Yuan; Sun, Ao; Cao, Jing-Yu; Wang, Zu-Sen (Frontiers in Pharmacology, 2025)
Liver cancer, especially primary liver cancer (PLC), stands as the third leading cause of cancer-related mortality globally, posing a significant threat to human health. Super-enhancers (SEs), clusters of enhancer elements with high histone modifications and transcriptional activity levels, play crucial roles in diverse biological processes and are closely associated with the pathogenesis of various diseases, including liver cancer. This review first delves into the pathogenic mechanisms of super - enhancers in liver cancer. SEs can drive the aberrant expression of oncogenes in liver cancer. Through interactions with transcription factors and chromatin-modifying enzymes, SEs can reshape the chromatin architecture, facilitating the access of transcriptional machinery to oncogene promoters and resulting in their overexpression. Additionally, abnormal activation of signaling pathways in liver cancer can also regulate the formation and activity of SEs, creating a positive - feedback loop that fuels tumor development. We further explore how targeting SEs may translate into clinical applications for liver cancer. Therapeutic strategies, such as using small inhibitors that disrupt the function of key components in SE-mediated transcriptional complexes, have shown promise in pre-clinical studies. These inhibitors can specifically block the activity of SEs, leading to the downregulation of oncogene expression and subsequent suppression of tumor cell growth. In addition, gene-editing technologies provide new tools for precisely modulating super-enhancer activity in liver cancer cells. By deleting or modifying specific enhancer elements within SEs, the expression of oncogenes can be effectively controlled. In conclusion, understanding the pathogenic mechanisms of SEs in liver cancer and their clinical applications offers a new perspective on the diagnosis, treatment, and prognosis of liver cancer. However, more in-depth research is required to fully realize the potential of super-enhancer-targeted therapy in clinical settings in order to provide more effective treatment options for liver cancer patients.